RELATIONSHIP OF CUSTOMER AWARENESS AND EXPECTATION IN DETERMINING THE ACTUAL UTILIZATION OF BANKING SERVICES - THRISSUR DISTRICT. - P. R. JEYALAKSHMI,; A. S. LAKSHMI RANI, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study attempts to measure (customers' perspective) awareness and expectation in determining the actual utilization of various banking services provided by public and private sector banks. Descriptive Research Design was utilized to determine customers' expectation level and awareness level with special reference to Thrissur district. A survey has been conducted by using Google forms to collect primary data and 96 questionnaires from PSBs and Private banks together were used in doing final analysis. Excel and SPSS software was used to measure, analyze and interpret the data. As the customer awareness level increases, their expectations level on the banking services shall increase accordingly and thereby the utilization level. Bankers should frequently keep an eye on the level of fulfillment of customers' personal needs and satisfaction, if they want the customers to endure loyal.